Sport-specific performances in elite youth sport climbers; gender, age, and maturity specifics - Gilic, B.; Vrdoljak, D. (Biomedical Human Kinetics, 2023)
Study aim: The increase in the number of professional climbers led to the development of climbers since early age. Therefore, the average age of elite climbers has decreased over the last decade. Consequently, age and maturity specifics should be inves-tigated with the influential factors in climbing. This research aimed to investigate the forearm muscle strength in youth sport climbers and determine the gender, age, and maturity status as factors of influence on forearm muscle performance in elite youth climbers.